1983
DOI: 10.1136/jcp.36.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of neutrophil chemotaxis by serum from patients with chronic lymphoproliferative disease.

Abstract: SUMMARY The sera of 74 individuals with chronic lymphoproliferative disease were screened for the presence of inhibitory activity against neutrophil chemotaxis. This was present in more than half the patients with IgA myeloma and Hodgkin's disease but was less common in chronic lymphocytic leukaemia, lymphocytic lymphoma and non-IgA paraproteinaemia. Heating the sera prior to testing frequently enhanced inhibitory activity particularly in myeloma and lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In addition to intrinsic PMN defects, certain unknown factors in the serum of patients with cancer appear to reduce the capacity of PMN to perform their main functions by blocking their Fc receptors373 or by reducing PMN chemoattraction; this has been reported in hepatocellular carcinoma,374 in other solid tumors,375–377 and in lymphoproliferative disease 339, 376, 378, 379. Serum from patients with solid tumors reduces the cytostatic activity of normal PMN 34.…”
Section: Does Defective Pmn Function Encourage the Growth Of A Canmentioning
confidence: 99%
“…In addition to intrinsic PMN defects, certain unknown factors in the serum of patients with cancer appear to reduce the capacity of PMN to perform their main functions by blocking their Fc receptors373 or by reducing PMN chemoattraction; this has been reported in hepatocellular carcinoma,374 in other solid tumors,375–377 and in lymphoproliferative disease 339, 376, 378, 379. Serum from patients with solid tumors reduces the cytostatic activity of normal PMN 34.…”
Section: Does Defective Pmn Function Encourage the Growth Of A Canmentioning
confidence: 99%
“…6-11 Our study demonstrated notable qualitative differences in phagocytosis against common bacterial but not fungal pathogens between the CLL patients and age-matched controls. Due to the small number of patients with infections, we were not able to identify a relationship between impaired PMN killing response and infection risk.…”
Section: Resultsmentioning
confidence: 63%
“…1-5 However, genetic or acquired deficiencies in innate cellular immune responses in heavily pretreated CLL patients may predispose them to severe, frequently fulminant infections. 6-11 Therefore, we sought to characterize the qualitative polymorphonuclear neutrophil (PMN)-associated immune impairment in CLL patients with a focus on differences in phagocytic killing by PMNs of key nonopsonized bacterial ( Staphylococcus aureus and Pseudomonas aeruginosa ) and fungal ( Candida albicans and Aspergillus fumigatus ) pathogens that frequently cause severe infections in CLL patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the innate immune response to tissue injury or infection, neutrophils are recruited to the inflammatory site. Neutrophil chemotaxis inhibitors were found in the sera of myeloma patients ( 22 ). In immunotherapy against MM, positive regulation of T-cell proliferation played a crucial role.…”
Section: Discussionmentioning
confidence: 99%